2023
DOI: 10.3847/2041-8213/acb7f1
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Long-range Active Galactic Nuclei (AGNs) Feedback Affects the Low-redshift Lyα Forest

Abstract: Active galactic nuclei (AGNs) feedback models are generally calibrated to reproduce galaxy observables such as the stellar mass function and the bimodality in galaxy colors. We use variations of the AGN feedback implementations in the IllustrisTNG (TNG) and Simba cosmological hydrodynamic simulations to show that the low-redshift Lyα forest can provide constraints on the impact of AGN feedback. We show that TNG overpredicts the number density of absorbers at column densities N HI < 1014 cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 77 publications
3
21
1
Order By: Relevance
“…Additionally, absorbers at the highest CDs are rarer, which makes them difficult to study both observationally and in the small-box (25 Mpc h −1 ) 3 CAMELS simulations. Tillman et al (2023) found that, at least for TNG, the CAMELS boxes produce a converged CDD as compared to the original TNG100-1 simulation, within observational error bars.…”
Section: Synthetic Spectramentioning
confidence: 61%
See 3 more Smart Citations
“…Additionally, absorbers at the highest CDs are rarer, which makes them difficult to study both observationally and in the small-box (25 Mpc h −1 ) 3 CAMELS simulations. Tillman et al (2023) found that, at least for TNG, the CAMELS boxes produce a converged CDD as compared to the original TNG100-1 simulation, within observational error bars.…”
Section: Synthetic Spectramentioning
confidence: 61%
“…We generate 5000 sightlines randomly placed in each simulation box-a number found to be sufficient for avoiding variations due to sampling (Tillman et al 2023). We do not add noise to the spectra generated from the simulation box.…”
Section: Synthetic Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…While all three of these simulations show a decline in the incidence rate of O VI absorption as a result of integrated black hole feedback, they implement the feedback in different ways (Schaye et al 2015;Weinberger et al 2017;Davé et al 2019). The feedback schemes lead to different values for bulk CGM properties such as CGM mass as a fraction of halo mass (e.g., Davies et al 2021;Tillman et al 2023). It is therefore plausible that while black hole feedback is involved in all three cases, the actual mechanisms by which O VI incidence is suppressed are not the same.…”
Section: Galaxy Quenching and Cgm Transformationmentioning
confidence: 99%